Новый учебник истории России (2023) как инструмент государственной пропаганды: некоторые ключевые нарративы - Starodubtseva, Anastassiya (Slavia Orientalis, 2026)
The article analyses the Russian history textbook for 11th-grade students, written by Vladimir Medinsky and Anatoly Torkunov, and introduced into Russian schools in 2023. The textbook is of particular interest due to its pronounced ideological orientation and the presence of propagandistic narratives that mirror those found in pro-government Russian media discourse. The aim of the article is to examine the key narratives, rhetorical strategies, and ideological markers present in the textbook, with a focus on how they construct interpretations of Russia’s relations with the West, Ukraine, and the so-called ‘special military operation’. Content and discourse analysis methods are employed to uncover the mechanisms through which these narratives and markers function as tools of state propaganda and political indoctrination.